Problems affecting the efficiency of animal disease reporting system in Oyo State, Nigeria (2009)
The planning and implementation of disease control and eradication program depend on efficient disease information system. Disease reporting can serve as an early warning mechanism against disease outbreak and spread. The problems and factors affecting the animal disease reporting system of Oyo state were diagnosed and identified by the use of open-ended interview and retrospective survey of records of outbreaks as kept in the offices of the three stages of disease reporting for the state. The major impediments confronting the animal disease reporting system’s operations of the state include inadequate qualified veterinary personnel, lack of communication facilities and poor diagnostic facilities. Based on the findings of this study, recommendations were made on improving the veterinary services; provision of communication facilities; farmers’ awareness; diagnostic capabilities; education and enforcement of existing veterinary laws, to improve the system’s operation for optimum effectiveness.